a-b=56
b=a:3
a=?
b=?
Răspunsuri la întrebare
Răspuns de
1
a - b = 56 si b = a : 3 ⇔ a = 3b
↓
inlocuim in prima egalitate ... 3b - b = 56
2b = 56
b = 28
↓
a = 3*28 = 84
Proba: a-b=56 adica: 84 - 28 = 56 (A)
b=a:3 adica; 28 = 84:3=28 (A)
↓
inlocuim in prima egalitate ... 3b - b = 56
2b = 56
b = 28
↓
a = 3*28 = 84
Proba: a-b=56 adica: 84 - 28 = 56 (A)
b=a:3 adica; 28 = 84:3=28 (A)
alitta:
Cu placere !
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă